Complement factor B is critical for sub-RPE deposit accumulation in a model of Doyne honeycomb retinal dystrophy with features of age-related macular degeneration. Issue 2 (9th August 2022) - Crowley, Maura A; Garland, Donita L; Sellner, Holger; Banks, Angela; Fan, Lin; Rejtar, Tomas; Buchanan, Natasha; Delgado, Omar; Xu, Yong Yao; Jose, Sandra; Adams, Christopher M; Mogi, Muneto; et al.
Abstract: EFEMP1 R345W is a dominant mutation causing Doyne honeycomb retinal dystrophy/malattia leventinese (DHRD/ML), a rare blinding disease with clinical pathology similar to age-related macular degeneration (AMD). Aged Efemp1 R345W/R345W knock-in mice ( Efemp1 ki/ki ) develop microscopic deposits on the basal side of retinal pigment epithelial cells (RPE), an early feature in DHRD/ML and AMD. Here, we assessed the role of alternative complement pathway component factor B (FB) in the formation of these deposits. RNA-seq analysis of the posterior eyecups revealed increased unfolded protein response, decreased mitochondrial function in the neural retina (by 3 months of age) and increased inflammatory pathways in both neural retina and posterior eyecups (at 17 months of age) of Efemp1 ki/ki mice compared with wild-type littermate controls. Proteomics analysis of eye lysates confirmed similar dysregulated pathways as detected by RNA-seq. Complement activation was increased in aged Efemp1 ki/ki eyes with an approximately 2-fold elevation of complement breakdown products iC3b and Ba ( P < 0.05). Deletion of the Cfb gene in female Efemp1 ki/ki mice partially normalized the above dysregulated biological pathway changes and oral dosing of a small molecule FB inhibitor from 10 to 12 months of age reduced sub-RPE deposits by 65% ( P = 0.029). In contrast, male Efemp1 ki/ki mice had fewer sub-RPE deposits than age-matched females, no elevation of ocular complement activation and no effect of FB inhibition on sub-RPE deposits. The effects of FB deletion or inhibition on Efemp1 ki/ki mice supports systemic inhibition of the alternative complement pathway as a potential treatment of dry AMD and DHRD/ML.